CALC

posted by .

find the following derivatives:

f(x) = (2x+5)/(x^2-3)

f'(x)= (2)*(x^2 -3)-(2x+5)*2x/(x^2-3)^2

is that correct???

f(x)= (lnx)(cos x)

f'(x)= 1/x*-sinx
or do i have to use the product rule??

thank you.

  • CALC -

    f'(x)= (2)/(x^2 -3)-(2x+5)*2x/(x^2-3)^2
    see the first term.

    next one
    use the product rule.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    find the following derivatives: f(x) = (2x+5)/(x^2-3) f'(x)= (2)*(x^2 -3)-(2x+5)*2x/(x^2-3)^2 is that correct?
  2. calculus

    Could someone check my reasoning? thanx Find the derivative of the function. sin(sin[sinx]) I need to use the chain rule to solve. So I take the derivative sin(sin[sinx) first. Then multiply that by the inside which is the derivative
  3. Calculus

    Find the derivative of y with respect to x. y= [(x^5)/5]lnx-[(x^5)/25] How would I go about doing this?
  4. Calculus (Derivatives)

    Using the product rule, find the derivative of the following function: (x^1/2 cscx sinx).
  5. Calc

    what are the first and second derivatives of y= sinx - 3^1/2 cos x for x in [0,2pi]
  6. College Calc

    Problem: y=sqrtx ^1/x. Find DY/DX. ln(f(x))=lnx^1/2x or lnx to the 1/2x 1/2x lnx product rule (1/4x^2)(lnx)+(1/x)(1/2x) is the product rule correct?
  7. Calculus

    Find the derivatives, dy/dx for the following functions. a. x^2y^4 = lnx + 3y b. y = ln(2x^2 + 1) c. y = ln(ãx) d. y = lnx/x e. y = x^2 lnx f. y ß log_2⁡(3x)
  8. Derivatives

    Find the derivatives of: 1. H(x)= sin2xcos2x The answer given is 2cos4x. My question is, how in the world did they get that!?
  9. Calculus

    Find the derivatives of the following 18. y=〖cos〗^4 x^4 ANSWER: tanx2 19. y= sinx/(1+ 〖cos〗^2 x) ANSWER: 3sinx 20. y=sinx(sinx+cosx) ANSWER: sinx Can you check my answers?
  10. Calculus

    Just got through with derivatives, power rule, and chain rule. I am supposed to find the first and second derivatives of the function. y = 4x/√x+1 and y = cos^2(x) y' = [(x+1)^(1/2)(4)]-[(4x)(1/2(x+1)^(-1/2))(1)] y' = [4(x+1)^(1/2)-4x]/[2(x+1)^(1/2)(x+1)] …

More Similar Questions